SOVEREIGN IMMUNITY OF NON-COMMERCIAL GOVERNMENT VESSELS AND DUE REGARD: CHINA COAST GUARD IN THE NATUNAS - Mangapul, Joy Henri; Idris, Idris; Dewi, Chloryne Trie Isana (Indonesian Journal of International Law, 2021)
Coastal states possess sovereign rights and jurisdiction within their Exclusive Economic Zone (EEZ), including the exercise of enforcement jurisdiction against foreign vessels conducting violations within the EEZ. However, certain ships are granted sovereign immunity and thus are not subject to coastal state’s jurisdiction. The United Nations Convention on the Law of the Sea (UNCLOS) only stipulated that injuries to the coastal state caused by activities conducted by a sovereign immune vessel will engage that vessel’s flag state responsibility. Indonesia had witnessed numerous violations within its EEZ, especially in waters around Natuna Islands. These violations are conducted by Chinese fishing vessels, which were escorted by China Coast Guard (CCG) vessels. Consequently violations by Chinese vessels would hamper Indonesia’s exercise of enforcement jurisdiction against Chinese fishermen caught committing illegal, unreported and unregulated fishing (IUUF), thus violating Indonesia’s sovereign rights and jurisdiction. This article discusses to what extent sovereign immunity applies to non-commercial government vessels, and whether they can be subjected to coastal state jurisdiction, should they hamper the exercise of coastal state’s enforcement jurisdiction within its EEZ. The article applies normative legal research by utilizing applicable regulations, theories, and existing practices. Sovereign immune vessels are required to pay due regard to other states, including coastal state. Activities constituting ‘abuse of rights’ jeopardizing coastal state’s exercise of enforcement jurisdiction will result in their flag state responsibility being invoked by the coastal state. This article recommends peaceful settlement of dispute through bilateral means, or multilateral means in the spirit of the 2002 Declaration of Conduct by pursuing a regional fisheries agreement.